The last caravans in antiquity: Camel remains from Caričin Grad (Justiniana Prima). (August 2021) - Marković, Nemanja; Ivanišević, Vujadin; Baron, Henriette; Lawless, Craig; Buckley, Michael
Highlights: The Caričin Grad is associated with the important Early Byzantine city Justiniana Prima inhabited only 80 years. Camel remains collection from Caričin Grad represents one of the largest so far discovered in the European antiquity context. The first use of ZooMS collagen fingerprinting analysis on the camel remains from the archaeological context. ZooMS collagen fingerprinting successfully determined camel hybrids. Camel hybrids from Caričin Grad were pack animals probably for civilian/trade use. Abstract: Camels played an important role in caravan traffic and long-distance communication during the early Byzantine period as indicated by new findings from Caričin Grad. Excavations at the site revealed the remains of an important early Byzantine city, which has been identified with Justiniana Prima founded in the 530 s by Justinian I (527–565). The city, created ex nihilo, in a rural area in the north-west of the province of Dacia Mediterranea, represents a distinctive example of late urbanisation. Given the existence of the city for only 80 years and the fact that the nearby locality remained uninhabited until modern times, the site has yielded well-preserved monuments and remains of material culture. They allow for a detailed study of the urbanism, architecture, material culture and other aspects of daily life from the second quarter of the 6th century to the beginning of the 7th century. Here we investigate the camel remains discovered in five locations in Caričin Grad. Morphometric and proteomic analyses, including both collagen peptide mass fingerprint analysis (ZooMS) as well as in-depth sequencing, revealed that the majority originate from hybrids of the dromedary and Bactrian camels. Supported by written sources from the Early Byzantine period, it appears as though the use of the Caričin Grad camels was primarily for civilian purposes. These results highlight the complementarity of morphometric and proteomic approaches and their value in better understanding the impact of the early Byzantine economy.